DIGITAL TRANSFORMATION AND BUSINESS PROCESS IMPROVEMENT IN SCHOOL LITERACY ECOSYSTEMS: INSIGHTS FROM ELIS (SCHOOL LITERACY ECOSYSTEM) IMPLEMENTATION IN JAKARTA, INDONESIA.: Inggris - Muhamad Ramadhona Rama; Awang Darmawan Putra (Journal of Management and Leadership, 2026)
The COVID 19 pandemic accelerated digital transformation across various sectors, including education. Previous studies on Chinese cross border e commerce SMEs demonstrated that organizations capable of surviving and growing during and after the pandemic were not merely technology adopters but organizations that fundamentally transformed their business processes, service delivery mechanisms, and value creation systems. Drawing upon Digital Transformation Theory and Harrington’s Business Process Improvement (BPI) framework, this article examines the implementation of the School Literacy Ecosystem (Ekosistem Literasi Sekolah—ELIS), developed by Generasi Cerdas Indonesia (GCI), as a case of digital transformation in educational institutions. Through conceptual analysis, this study demonstrates how ELIS transforms conventional school literacy practices into a digital literacy ecosystem that integrates content creation, digital publishing, knowledge dissemination, and economic value generation. The findings suggest that ELIS represents not only a digital library initiative but also a comprehensive business process redesign capable of creating sustainable educational and economic impacts. The study contributes to the growing discourse on educational digital transformation and knowledge based economic ecosystems in emerging economies.